Pengenalan Pakaian Adat Aceh Berbasis Augmented Reality Menggunakan Metode Speed Up Robust Featured (SURF) - gunawan, chicha rizka; Nurdin, Nurdin; Fajriana, Fajriana (Jurnal Komtika (Komputasi dan Informatika), 2023)
Aceh Province, especially Langsa City, has a tourist attraction, namely the Langsa City Forest Park House (RTH). One of the most interesting rides in Langsa City Forest Park is Rumoh Aceh. Based on the results of visits and interviews by Rumoh Aceh officers, the large number of visitors from outside Aceh with one officer sometimes made it difficult for the officers to explain the information available about Rumoh Aceh, especially Acehnese traditional clothes, which were only displayed from a printed image, and provided no other information about these traditional clothes, so that many visitors did not know the diversity of designs and motifs of traditional clothes in Aceh. So, a medium was formed that could display Acehnese traditional clothing. The media uses augmented reality technology so that users can add virtual objects to the real environment to make it easier to use. This application uses the Speed Up Robust Featured (SURF) algorithm, which can process marker tracking quickly so that it can obtain better tracking speed times. The shortest distance from the marker to the camera that can show 3D objects is 20 cm, whereas the farthest distance that cannot show 3D objects is 100 cm. The best distance at which a marker can be detected is 20–80 cm. The best average detection time is 0.00049 s, and the average speed obtained is 1261.22 m/s at a distance of 60 cm. The Speed Up Robust Featured (SURF) algorithm can be used in the Augmented Reality-based Aceh Traditional Clothing Recognition application.